REVIU PENGADAAN TANAH DALAM PENGEMBANGAN KAWASAN EKONOMI KHUSUS: TINJAUAN DARI CHINA, INDIA DAN AFRIKA: TINJAUAN DARI CHINA, INDIA DAN AFRIKA - Ramadhan, Bagus; M. Sani Roychansyah; Bambang Hari Wibisono (LPPM Universitas Terbuka, 2023)
Land acquisition is one of the aspects and problems in Special Economic Zones (SEZ)development. In this paper will explain another case of land acquisition problem in specialeconomic zones development or in general industrial area development located in China,India and Africa from literature review using Harzing Publish or Perish software andVOSViewer. The result of this review from the three location shows that land developmentin SEZ development have strong connection with land acquisition policy. With clear andstrong policy framework can give legal certainty for affected communities, investor orgovernment as regulator of land acquisition process.